The Suspension of Death: the cryonic utopia in the context of the U.S. funeral culture - Krüger, Oliver (Marburg journal of religion, 2010)
This article outlines the history of cryonics, starting with fictional novels and movies and the actual formation of the cryonic movement in the 1960s. Cryonics has been considered - by its advocates - to overcome religion by offering a technological way of immortality. Since cryonics never gained serious attention outside the United States it is promising to ask for the specific frame of American funeral culture as a condition for the emergence (and the limitations) of cryonics.